PEMBERIAN WASIAT WAJIBAH KEPADA ISTERI NON-MUSLIM (Analisis Putusan Mahkamah Agung Nomor 16 K/AG/2010) - Nur Fazila; Muchlis bahar; elfia (Syakhsia Jurnal Hukum Perdata Islam, 2024)
A mandatory will is a gift of inheritance given to heirs who do not get a share of the inheritance left by the heir. Usually those who get a share of the inheritance are adopted children or adoptive parents, but in jurisprudence Number 16K/AG/2010 wives who are non-religious Muslims by the supreme court receive a share of the inheritance in the form of a mandatory will. This type of research is normative legal research, namely legal research carried out by examining library materials or secondary data. This research is descriptive analysis with the method used in this research, namely normative juridical. The data source is primary legal material originating from Supreme Court decision Number 16 K/AG/2010, and secondary legal material comes from books, journals and articles related to this research topic RI Supreme Court Decision No.16 K/AG/2010 , the Supreme Court of Justice is of the opinion that the Decision of the Makasar High Religious Court Number 59/Pdt.G/2009 which upholds the decision of the Makasar Religious Court Number 732/Pdt.G/2008 is cancelled. Furthermore, the Panel of Judges of the Supreme Court decided to try this case themselves. The Supreme Court judge stated that Evie Lany Mosintah (wife) received 1/2 part of the joint assets and the other 1/2 part was the inheritance which became the share of the deceased's heirs. Evie Lany Mosintah, who initially did not receive an inheritance from the deceased through the decision of the Makasar Religious Court and the Makasar Religious High Court, was determined by the Panel of Judges at the Supreme Court that Evie Lany Mosintoh received a share of the inheritance through a mandatory will, whose share was ¼.